Federal Republic of Germany : Adjustment in a Surplus Country, Occ. Paper No. 64. (Occasional Papers; Occasional Paper ;, 1989)
This chapter reviews recent economic developments and economic prospects in which the emergence of the principal imbalances is traced, and their persistent character highlighted in the Federal Republic of Germany. On macroeconomic policies, while one might quibble about the rate of expansion of the money supply or the timing of tax reduction and reform, the paper does not find major errors in the formulation or implementation of policies that would account for the principal economic imbalances. The need to reduce rules and regulations, which act to limit the flexibility and dynamism of the German economy, has been reinforced by the objective of fully liberalizing trade in services within the European Community by 1992. The banking industry is exempt from the provisions of the antitrust law, which prohibits restraints on competition, price collusion, and other collusive agreements. Among economists, there is a broad agreement that structural reforms in Germany would greatly improve economic performance and contribute to external adjustment.